Pemanfaatan Konsep Geometri dan Teori Graf pada Strategi Memenangkan Permainan Tradisional Margala - Sorta Corie Ivana Panjaitan; Hasratuddin Hasratuddin; Bornok Sinaga (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Ethnomatics integrates local culture in mathematics learning. Traditional games become ethnomatic when used as a means of learning mathematics. In the Simalungun area, a traditional margala game competition was held. In the margala game there is an educational element, through the margala game the player's character values ​​can be developed. Margala games can be created to improve understanding of Mathematics subjects, moreover by applying mathematics during the game, the chances of winning the game are greater. Through this research, it can be seen the closeness of mathematics to local culture. This research aims to find strategies to get points when you are on the attacking team and to prevent getting points when you are on the guard team. to win the traditional game of margala, by utilizing concepts in mathematics, namely Geometry and Graphs. The research was carried out through literature study, observation, interviews, field notes and documentation on the players and coaches of the margala team at SMP Negeri 3 Jorlang Hataran and continued by analyzing the data. The use of geometric concepts in traditional margala game strategies, obtained by understanding the concepts of area and perimeter in rectangular shapes related to the length of the player's hand or reach, as well as position on the field can produce an effective strategy for winning the game. Apart from that, by using graph theory you can predict your opponent's movements and find the shortest route and avoid being touched by your opponent.